Credential Effectiveness to Improve Nurses Competency: A Systematic Review - Hardityo Fajarsiwi; Nursalam Nursalam; Andri Setiya Wahyudi (Universitas STRADA Indonesia, 2021)
This study reviewed the effectiveness of credentials test on nurses’ competencies. A systematic review was conducted with The Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) approach. It broadly used Scopus, Science Direct, and ProQuest database. The inclusion criteria in the literature study were: original article, journal article, article in English, and available in full text from international databases; Ebsco, Science Direct, Scopus, SAGE, PubMed, and ProQuest. obtained total of 310 articles were obtained, and 15 were considered relevant for this systematic review and limited for the last five years, 2015 to 2020. The articles’ quality were evaluated using the Joanna Briggs Institute (JBI) for experimental study type. A total of 15 articles were reviewed. This study found that credentials were effective in improving nurses' clinical competence, professional competence and general competence that could be used in nursing services